A history of Palestine, 634-1099 - Gil, Moshe 1921- (Cambridge University Press, 1997)
This is the first comprehensive history of Palestine from the Muslim conquest in 634 to that of the Crusaders in 1099. It is a translation and revised version of volume I of Palestine during the first Muslim period which was published in Hebrew in 1983 and presents an authoritative survey of the early mediaeval Islamic and Jewish worlds. Professor Gil begins by reviewing the political and military events in Palestine before and after the Arab invasion. Later chapters explore the Abbasid, Tulunid, Ikhshidid and Fatimid periods, during which time Palestine was an almost perpetual battlefield for states, armies and factions. Against this backdrop of conflict and administrative changes, the author portrays the everyday life of Palestine and its inhabitants. He looks at the economic history of Palestine--its agriculture, transport facilities, exports and systems of taxation--as well as the religious status of Jerusalem, the nature of Islam's tolerance towards Jews and Christians and the status, leadership and customs of the Christian populace. Specific attention is paid to the history of Palestinian Jews under Muslim rule. Professor Gil details their topography, economic activities and religious life; he explores the Karaite and Samaritan communities and discusses the role of the most prominent Jewish institution, the yeshiva. A history of Palestine, 634-1099 is based on an impressive array of sources. Professor Gil has put to use more than one thousand documents of the Cair Geniza collection and these are paralleled by Arabic, Syriac, Latin and Greek material. This monumental study will be an essential resource for students and specialists of mediaeval Islamic and Jewish history and religious studies and for anyone interested in the history of the Holy Land